2009
DOI: 10.1109/tdei.2009.4784573
|View full text |Cite
|
Sign up to set email alerts
|

Fast and slow charge packets in polymeric materials under DC stress

Abstract: The presence of slow space charge packets crossing the insulation thickness from one electrode to the other and causing significant electrical field distortion has been reported already in several papers. They are activated in general by very high DC fields or, in highly polluted materials, by relatively low fields and constitute an important ageing factor, concerning DC electrical stress. It has been observed, in fact, that such packets can cause accelerated breakdown of insulation.The development of fast sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 29 publications
0
70
1
Order By: Relevance
“…These experiments were performed on 0.3 mm flat slabs in a PEA system with a carbon-loaded polyethylene as the high voltage electrode but aluminum as the earth electrode above the piezo-electric sensor. Preliminary results were presented in Fabiani et al 47 and more details are given in Montanari et al 48 Soliton pulses of both polarity were observed in all of the Bohemite loaded samples at E ¼ 20MV/m and 30MV/m and temperatures of 293 -313 K with a magnitude (1À2 Â 10 À6 Cm À2 ) that was much smaller than those observed in the XLPE-insulated mini-cable, but with similar repetition rates. In these materials also we confirmed the correlation between the charge solitons measured via the PEA system and current pulses.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…These experiments were performed on 0.3 mm flat slabs in a PEA system with a carbon-loaded polyethylene as the high voltage electrode but aluminum as the earth electrode above the piezo-electric sensor. Preliminary results were presented in Fabiani et al 47 and more details are given in Montanari et al 48 Soliton pulses of both polarity were observed in all of the Bohemite loaded samples at E ¼ 20MV/m and 30MV/m and temperatures of 293 -313 K with a magnitude (1À2 Â 10 À6 Cm À2 ) that was much smaller than those observed in the XLPE-insulated mini-cable, but with similar repetition rates. In these materials also we confirmed the correlation between the charge solitons measured via the PEA system and current pulses.…”
Section: Discussionmentioning
confidence: 92%
“…Their repetition rate was found to be dependent only upon temperature and electric field, as will be shown in the following, see Tables I-IV. Measurements made every 25 ms for the first minute of voltage application allowed between 100 and 200 such pulses of each polarity to be observed. It was noted that: (a) the shape of each pulse was retained during its transit of the insulating layer, (b) the amplitude of the pulses exhibited a polarity dependence though all pulses of the same polarity had the same amplitude and showed little dependence upon field and temperature, 23 (c) the speed of transit was independent of radial position (within our time resolution) but depended upon temperature and field and polarity, (d) the pulse repetition rate was polarity dependent at the same temperature and field, resulting in situations where both a positive and negative pulse moving in opposite directions were present in the XLPE layer at the same time, Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the applied field exceeds the threshold for space charge accumulation, charge injected from the electrodes can accumulate in traps located at the interface with electrodes and in the insulation bulk [1][2][3][4][5].The existence of such a threshold would have considerable impact on the design of insulation systems. Designing an insulation system for an electrical stress below the threshold would assure very long life and high reliability, provided that there are no other significant stresses acting on the insulation.…”
Section: Introductionmentioning
confidence: 99%